Korelasi antara Kualitas Sistem Informasi Penjualan dengan Kinerja Pengguna - Cahyadi, Raden Adi; Nardo, Leo; Suryanto, Suryanto; Sabrina, Cecilia (Bina Nusantara University, 2013)
The research aims to determine whether there is a relationship between the quality of sales information systems and user performance. The research method uses survey correlation techniques. Data are collected using a questionnaire previously calibrated to test the validity (product moment) and instrument reliability (Alpha Cronbach). The population used is users of information systems that are sales employees. There is a total sample of 20 people obtained, with Non-Probability Sampling that is saturated sampling / survey. Data analysis is performed using regression techniques of simple linear and simple correlation. Prior to analysis, test of analysis requirements need to be done, which are normality and homogeneity test. The results show acorrelation coefficient of 0:51 or 51% which means that there is a positive relationship on medium level between the Effectiveness of sales Information Systems with Users performance. The coefficient of determination is 0:26or 26%. This means that 26% of the variation in user performance can be explained by the variable Effectiveness of Sales Information Systems. Meanwhile, the remainder which is 74% consists of factors (variables), such as leadership style, work environment, salary and others. It can be concluded from this research that there is a positive correlation (relationship) at medium level which is significant between the Effectiveness of Sales Information System with User Performance, which means that the higher the level of effectiveness of Sales Information System is, the higher the level of user performance will be.